Effect of Acupuncture on Neuroplasticity of Stroke Patients with Motor Dysfunction: A Meta-Analysis of fMRI Studies - Qiuyi Lv; Guixing Xu; Yuxin Pan; Tongtong Liu; Xiaodong Liu; Linqing Miao; Xing Chen; Lan Jiang; Jie Chen; Yingjia He; Rong Zhang; Yihuai Zou (Neural Plasticity)
Importance. Acupuncture is an effective treatment for stroke, especially in the aspect of motor deficit. Many brain imaging studies of acupuncture have found significant changes in brain function after acupuncture treatment in order to reveal its underlying mechanisms in regulating neural plasticity. However, no definite consensus has been reached. Objective. To analyze the pattern of intrinsic brain activity variability that is altered by acupuncture compared with conventional treatment in stroke patients with motor dysfunction, thus providing the mechanism of stroke treatment by acupuncture. Methods. Chinese and English articles published up to May 2020 were searched in the PubMed, Web of Science, EMBASE, and Cochrane Library databases, China National Knowledge Infrastructure, Chongqing VIP, and Wanfang Database. We only included randomized controlled trials (RCTs) using resting-state fMRI to observe the effect of acupuncture on stroke patients with motor dysfunction. R software was used to analyze the continuous variables, and Seed-based d Mapping with Permutation of Subject Images (SDM-PSI) was used to perform an analysis of fMRI data. Findings. A total of 7 studies comprising 143 patients in the treatment group and 138 in the control group were included in the meta-analysis. The results suggest that acupuncture treatment helps the healing process of motor dysfunction in stroke patients and exhibits hyperactivation in the bilateral basal ganglia and insula and hypoactivation in motor-related areas (especially bilateral BA6 and left BA4). Conclusion. Acupuncture plays a role in promoting neuroplasticity in subcortical regions that are commonly affected by stroke and cortical motor areas that may compensate for motor deficits, which may provide a possible mechanism underlying the therapeutic effect of acupuncture.